From Basic Science to Clinical Practice: The Role of Cancerous Inhibitor of Protein Phosphatase 2A (CIP2A)/p90 in Cancer - Chen, Beibei; Hu, Huihui; Chen, Xiaobing (Frontiers in Genetics, 2023)
Cancerous inhibitor of protein phosphatase 2A (CIP2A), initially reported as a tumor-associated antigen, so-called p90, is highly expressed in most solid and hematological tumors. The interaction of CIP2A/p90, protein phosphatase 2A (PP2A) and c-Myc can hinder the function of PP2A toward c-Myc S62 induction and therefore stabilize c-Myc protein, which is a potential role of CIP2A/p90 in tumorigenesis such as cell proliferation, invasion and migration as well as cancer drug resistance. The signaling pathways and regulation networks of CIP2A/p90 are complex, which were not completely understood so far. Many previous studies have also demonstrated that CIP2A/p90 can be used as a potential therapeutic cancer target. In addition, the autoantibody against CIP2A/p90 in sera may be used as a promising biomarker in the diagnosis of certain types of cancer. In this review, recent advances relating to the CIP2A/p90 was focused on for further study.